Peranan Mahasiswa KKN dalam Melaksakanan Kegiatan Pengabdian di Kelurahan Sukamaju, Kecamatan Sail, Kota Pekanbaru - Fithri, Radhiyatul; Simamora, Audina Yulianty; Nadella, Suraya; Siregar, Keani Isnaini; Asyidiq, Muhammad Arief; Wardana, Robby; Frisca, Dela; Febrian, Muhammad; Sitinjak, Mando; Safika, Nur; Fellycia Sihotang, Theresia Viona; Primayani, Rani; Ramadhan, Alif Rambang; Suryanata, Halim; Maulana, Fadlan Risdi; Utari, Putri Amanda; Nugraha, Muhammad Davin; Sugara, Roby; Febtrata, Adhabin; Muhammad, Rifqi; Togatorop, Agnesia; Permadani, Tasya; Maputra, Fikri Erwan; Hasyim, Suhail Hawari; Putri, Fara Dila (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
The Community Service Program (KKN) was one form of student dedication to society by applying academic knowledge to social life. The problem faced in Sukamaju Sub-district, Sail District, Pekanbaru City was the low awareness of the community regarding health, education, and environmental cleanliness. The purpose of this activity was to identify the role of KKN students in carrying out additional programs that supported local needs. The method used was descriptive qualitative through observation, interviews, and documentation. The results show that KKN students successfully implemented several programs, including posyandu (integrated health service), (religious education), group exercise, Independence Day competitions, the creation of mini trash bins, and a reading corner. These programs provide positive impacts by raising health awareness, strengthening religious values, encouraging environmental care, and fostering togetherness. In conclusion, KKN students play an essential role in enhancing community participation through educational, participatory, and sustainable programs.